The Effect of Self-Esteem on Fear of Missing Out In Early Adult Vape Pod Users - Vania Husni Nasyita; Lilis Ratnasari (Jurnal Sosial Humaniora dan Pendidikan, 2026)
Along with current developments, switching from tobacco cigarettes to electronic cigarettes (vapes) has become an increasingly popular trend in various circles of society, which has resulted in the emergence of Fear of Missing Out behavior and Self-Esteem as a benchmark for assessing a person's FoMO level. This study aims to determine the influence of Self-Esteem on Fear of Missing Out in early adult vape pod users. This study is a quantitative study using a simple regression analysis technique. The sample in this study consisted of 127 respondents who were early adult active vape pod users. The data collection technique used was purposive sampling with the criteria of male/female, aged 20-40 years, active vape pod users. Based on the results of the study, showing a significance value of 0.000 (p<0.01), with a contribution of 11,2% based on the results of the study, the hypotesis in this study is accepted, namely there is a very significant influence of self-esteem on fear of missing out in early adult vape pod users.